A Micro-Level Analysis of Support in Britain for the War in Afghanistan. (May 2014) - Clements, Ben
Research Highlights and Abstract The article conducts a detailed and robust analysis of the social and attitudinal underpinnings of general support for the war in Afghanistan. The article contributes to scholarly understanding of public attitudes in Britain on foreign policy issues and to the wider literature on public opinion and war. The findings underline the long-standing 'gender gap' in attitudes to war, with men more in favour. Labour partisanship and political knowledge are directly related to support for the war, though there is only weak evidence that the effects of partisanship are mediated via political knowledge. This article analyses the micro-level factors affecting public opinion in Britain towards the long-running war in Afghanistan, a major foreign policy issue in the post-9-11 era. It examines the effects of social and attitudinal factors, including perceptions of how the war is going. There is a strong evidence of a 'gender gap', with men more in favour, while those with higher educational attainment are more supportive. Perceptions of the war's progress play a strong role in shaping general support. Labour partisans are more supportive while political knowledge is positively-related to support for the war. There is weaker evidence that the effects of partisanship are mediated via political knowledge. This article contributes to the scholarly understanding of public attitudes in Britain on foreign policy issues and to the wider literature on public opinion and military intervention.